A new acentric borate of K2Ba[B4O5(OH)4]2·10H2O: synthesis, structure and nonlinear optical property. (2nd October 2016) - Lin, Feng; Dong, Yaping; Peng, Jiaoyu; Wang, Liping; Li, Wu; Yang, Bo
Abstract : A new acentric mixed metal borate of composition K2 Ba[B4 O5 (OH)4 ]2 ·10H2 O, has been successfully obtained by slow evaporation solution method. The compound crystallizes in the Orthorhombic space group Pna21 (No.33) with a = 16.8668(7) Å, b = 13.0903(5) Å, c = 11.5529(5) Å and Z = 4. [B4 O5 (OH)4 ] 2− clusters serve as fundamental building unit linking with BaO8, K1O6, K2O7 by common O atoms to form three-dimensional layer structure. The second harmonic generation measurements in the powder samples reveal that the compound exhibits approximately 0.5 times that of KH2 PO4 (KDP) and phase matching.